Leveraging Artificial Intelligence in Assessments - Arantxa Barnard; Nathalie Cupido (Journal of Ethics in Higher Education, 2025)
The utilisation of artificial intelligence (AI) in assessments is making headway and is increasingly changing the landscape of the field of education. The leaders and policymakers of higher education institutions should be cognisant of their significant role in ensuring that AI is used responsibly and ethically and implemented with human oversight. The two objectives of this study were firstly to determine the lecturer’s perspectives and experiences with implementing the Traffic Light Model in assessments. Secondly, the lecturer’s insights should be leveraged to inform policy development and further implementation of TLM in the institution. The results of this inquiry provided a platform for policymakers to acknowledge and review the improvements that can be made with implementing the Model.